Hubungan Persepsi Siswa Terhadap Kompetensi Pedagogik Guru Dengan Hasil Belajar PPKn Siswa Kelas V - Khaerunnisa, Khaerunnisa; Hartoto, Hartoto; Sulfana, Sulfana (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This study aims to describe the pedagogical competence of class V teachers of SDN 1 Manjalling, Kecamatan Bajeng Barat, Kabupaten Gowa, an overview of PPKn learning outcomes of grade V students of SDN 1 Manjalling, West Bajeng District, Gowa Regency and a significant relationship between teacher pedagogic competence and PPKn learning outcomes of grade V students of  Kecamatan Bajeng Barat, Kabupaten Gowa. This research is a quantitative approach. Data on pedagogic competence were obtained through questionnaires or questionnaires collected from all students of class V. While the learning outcomes of PPKn students were obtained through documentation in the form of odd semester test documents in class V students.